2008
DOI: 10.30638/eemj.2008.096
|View full text |Cite
|
Sign up to set email alerts
|

Management of Waste in Rural Areas of Gorj County, Romania

Abstract: On the top of the ecological priority list in Romania, waste management is on the third place following the problems regarding the surface and underground water pollution, as well as that of the atmosphere. The clean-up of the landscape represents an issue largely discussed in Romania. The paper presents the advantages of waste management for the landscape, which includes: waste gathering and transfer, waste selection, waste biological treatment and the storage. Some analyses of the constituent components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The measured absorption spectra also represented that the strong absorption bands of the Cu-related defect centers were located centering at VIS and UV region with an extension up to near infrared (NIR) region. In addition to the overall increase of optical absorption, distinct absorption bands peaking at 565 nm, 585 nm were also found to appear after the irradiation, and they are identical to the surface plasmon resonance (SPR) absorption of Cu metal particles in the previous reports [16][17][18]24]. Thus Cu 2+ ions in the optical fiber core were thought to be converted to Cu metal particles by the irradiation as following reduction reaction: Cu 2+ + 2e À = Cu.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The measured absorption spectra also represented that the strong absorption bands of the Cu-related defect centers were located centering at VIS and UV region with an extension up to near infrared (NIR) region. In addition to the overall increase of optical absorption, distinct absorption bands peaking at 565 nm, 585 nm were also found to appear after the irradiation, and they are identical to the surface plasmon resonance (SPR) absorption of Cu metal particles in the previous reports [16][17][18]24]. Thus Cu 2+ ions in the optical fiber core were thought to be converted to Cu metal particles by the irradiation as following reduction reaction: Cu 2+ + 2e À = Cu.…”
Section: Resultsmentioning
confidence: 66%
“…And we have found that the Cu ions are involved in the formation of radiation-induced defect centers in the optical fiber that affect the magneto-optical properties. Moreover, a number of studies have also shown that Cu ions in silicate glasses were reduced to those with lower valences by the thermal treatment, the gamma-ray irradiation, and the ion-exchange techniques, which contributed to the change in magneto-optical properties of the glasses [14][15][16][17][18]. Therefore, we have chosen Cu-doped germano-silicate optical fiber to investigate the influence of gamma-ray irradiation on magneto-optical properties, particularly on Faraday effect.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing and control emissions of sulfur oxides from combustion and industrial processes can be achieved by applying several measures such as use of fuel with a low sulfur content, replacement of burning sulfur fuels with other energy sources, removing sulfur from fuels prior to burning and removing sulfur oxides from the flue gases [16,17].…”
Section: Fig 1 Location Of the Automatic Monitoring Station Gj-2 Romentioning
confidence: 99%
“…Recent data suggest that globally, air pollution is one of the largest environmental health risks being responsible for many diseases [2,[10][11][12][13][14][15].…”
mentioning
confidence: 99%